Evaluation of amplified ribosomal DNA restriction analysis as a method for the identification of Botryosphaeria species. - Alves, Artur; Phillips, Alan J L; Henriques, Isabel; Correia, António (FEMS microbiology letters, 2005)
The polymerase chain reaction was used to amplify a rDNA fragment containing the internal transcribed spacers (ITS1-5.8S-ITS2) and the D1/D2 variable domains of the 28S rDNA from 10 species of the genus Botryosphaeria (Fungi, Ascomycota). Restriction analysis of the amplicons with frequent-cutting endonucleases (amplified ribosomal DNA restriction analysis) allowed the definition of 12 rDNA haplotypes. Each of the rDNA haplotypes could be unambiguously assigned to a single Botryosphaeria species, thus allowing clear identification of all the species tested. Intraspecific polymorphism was very low and detected only in Botryosphaeria parva and Botryosphaeria dothidea. Cluster analysis of banding patterns of the isolates corresponded well with known species delineations. The method described in this paper provides a simple and rapid procedure for the differentiation and identification of Botryosphaeria isolates at the species level.
Keywords: ARDRA; Botryosphaeria; D1/D2 domains; ITS; rDNA; Species identification